Perbandingan Madrasah Nizhamiyah Dan Madrasah Tingkat Tinggi Al-Azhar Dalam Mencetak Intelektual Muslim - Siska Itaniyah H. (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2022)
Abstract: Madrasah Nizhamiyah was an educational institution that played an important role in the government of the Seljuq dynasty. This institution comes with the concept of Sunni Islam, to be able to balance the teachings of Shia Islam and its Mu'tazilah allies who want to influence the territory of the Seljuq dynasty. Regarding the role of Madrasah Nizhamiyah in spreading the Sunni school of thought, many sources say, however, from these various studies no clear explanation and explanation has been found. Talking about Madrasah Nizhamiyah, there are many problems in the Role of Madrasah Nizhamiyah during the Niham Al-Mulk Period 1065-1072 AD To answer this question, descriptive analytical method was used, through written sources (Library Research) with a historical approach. Speaking of al-Azhar, our eyes are fixed on the oldest Islamic educational institution which is still a reference for the community to study Islamic sciences in particular and general knowledge globally. As an educational institution, al-Azhar has many important roles in printing and delivering its alumni to become important people in various fields of life. Initially founded during the Fatimid dynasty in Egypt. Al-Azhar is a mosque building that is no different from other mosques in general that already existed at that time. However, al-Azhar apart from being a place of worship is also used to instill Shia Ismaili ideology. With the developed Shi'a school of thought, al-Azhar mosque became the printer and reinforcer of the Fatimiya dynasty.